Protein Interactions, Hydration and Solvation Structure in Osmolyte Solutions: Lysozyme in Free Amino Acids Solutions - Rahim, Abdoul; J. Jalkanen, K. (Current Physical Chemistry, 2014)
The influence and effects that the amino acids L-alanine, glycine and L-proline have on the structure, stability and hydration of lysozyme were analyzed using molecular dynamics (MD) with the CHARMM force field as implemented in the NAMD simulation package. The solution properties of lysozyme in the amino acid-water-protein solutions at room temperature and atmospheric pressure for six concentrations were compared with those of lysozyme in an aqueous solution at the same temperature and pressure. The properties of lysozyme are analyzed in terms of the preferential hydration concept as it applies to the water-protein hydrogen bonds and amino acid-protein hydrogen bonds. The radial distribution functions of the water and amino acid atoms in the neighborhood of lysozyme were used to monitor the preferential hydration. In addition, analysis of the solvent and amino acid atom distributions around lysozyme was used to investigate the make-up/composition of the protein-solution boundary/interface, that is, interfacial waters and/or interfacial amino acid in comparison to the interfacial waters in the protein-water solution. The structure and properties of the amino acids and/or water molecules near the protein surface are also investigated, as they need to be displaced when a ligand, cation, anion or other protein binds and/or interacts with lysozyme. Finally the osmolytic properties of these amino acid/lysozyme solutions in comparison to those of the aqueous lysozyme solution are discussed in terms of the stabilizing effects of lysozyme’s structure in aqueous solution under denaturing conditions: elevated temperature, and on drying, that is, during lyophilization, a common method to stabilize pharmaceutical protein formulations during storage and shipment.
Keywords: lysozyme